Tourism and Heritage in the Chornobyl Exclusion Zone - Banaszkiewicz, Magdalena (Heritage, Tourism, and Community, 2023)
Tourism and Heritage in the Chornobyl Exclusion Zone (CEZ) uses an ethnographic lens to explore the dissonances associated with the commodification of Chornobyl's heritage. The book considers the role of the guides as experience brokers, focusing on the synergy between tourists and guides in the performance of heritage interpretation. Banaszkiewicz proposes to perceive tour guides as important actors in the bottom-up construction of heritage discourse contributing to more inclusive and participatory approach to heritage management. Demonstrating that the CEZ has been going through a dynamic transformation into a mass tourism attraction, the book offers a critical reflection on heritagisation as a meaning-making process in which the resources of the past are interpreted, negotiated, and recognised as a valuable legacy. Applying the concepts of dissonant heritage to describe the heterogeneous character of the CEZ, the book broadens the interpretative scope of dark tourism which takes on a new dimension in the context of the war in Ukraine. Tourism and Heritage in the Chornobyl Exclusion Zone argues that post-disaster sites such as Chornobyl can teach us a great deal about the importance of preserving cultural and natural heritage for future generations. The book will be of interest to academics and students who are engaged in the study of heritage, tourism, memory, disasters and Eastern Europe.